2015
DOI: 10.1038/srep09722
|View full text |Cite
|
Sign up to set email alerts
|

Host-virus interaction: the antiviral defense function of small interfering RNAs can be enhanced by host microRNA-7 in vitro

Abstract: Small interfering RNAs (siRNAs) directed against poliovirus (PV) and other viruses effectively inhibit viral replication and have been developed as antiviral agents. Here, we demonstrate that a specific siRNA targeting the region between nucleotides 100–125 (siRNA-100) from the 5′-untranslated region (5′-UTR) of PV plays a critical role in inhibiting PV replication. Our data demonstrate that siRNA-100 treatment can greatly reduce PV titers, resulting in up-regulation of host microRNA-7 (miR-7), which in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…High-throughput screening revealed that at least 29 miRNAs were able to inhibit Sabin-2 replication. During the course of this study, other groups reported that PV transcript and protein levels were appreciably lower in ectopic miR-7 expressed in infected A549 cells (Zhang et al, 2015). However, miR-7 was not included in the 29 miRNAs found from our screening data to have antiviral activity.…”
Section: Discussionmentioning
confidence: 42%
“…High-throughput screening revealed that at least 29 miRNAs were able to inhibit Sabin-2 replication. During the course of this study, other groups reported that PV transcript and protein levels were appreciably lower in ectopic miR-7 expressed in infected A549 cells (Zhang et al, 2015). However, miR-7 was not included in the 29 miRNAs found from our screening data to have antiviral activity.…”
Section: Discussionmentioning
confidence: 42%
“…It has been reported that miR-7 is widely conserved in animal species and is up-regulated during invertebrates and vertebrate’s virus infection, such as poliovirus and white spot syndrome virus (WSSV). In crab, the miR-7 could inhibit host anti-viral immune response by targeting Myd88 to enhance WSSV replication [ 21 ], whereas the miR-7 up-regulation induced the inhibition of poliovirus infection in human cells [ 22 ]. Similarly, miR-7 was also found to be up-regulated in human influenza virus infection [ 23 ] and in H9N2 AIV infection in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in miRNA expression in MA104 cells and HT‐29 cells suggest a potential role of miRNAs in antiviral responses. Two recent works showed that miR‐7 could supplement antiviral effect [Zhang et al, ] and miR‐125a plays an important role in HBV infection [Mosca et al, ]. MiR‐7 and miR‐125a maybe has a potential role in anti‐rotavirus response.…”
Section: Discussionmentioning
confidence: 99%